Oral and Dental Health Problems of Children with Attention Deficit/Hyperactivity Disorders, and Solution Proposals - Ceylan Çağıl Yetiş; Zuhal Kırzıoğlu (Galenos Yayinevi, 2017)
Attention deficit and hyperactivity disorder (ADHD) is the most common childhood onset behavioral disorder characterized by a developmentally inappropriate attention deficit, hyperactivity-impulsivity or a combination of these. Genetic and environmental factors play a role in the etiology. Because of the behavioral problems sourced from the disease itself and side effects of the drugs used in therapy, children with ADHD take place in the risk group in terms of oral and dental health problems and they are included in the group of patients who need special attention in pediatric dentistry. Drugs used in the treatment are known to cause dry mouth. Children with ADHD have been reported to have low oral hygiene habits and a high prevalence of dental caries. Also, parafunctional habits such as bruxism and dental trauma are observed more frequently in these children. In this review, oral health and behavior management problems in children with ADHD are pointed out, and solutions are suggested.